The Innovative Milieus Approach: Toward a Territorialized Understanding of the Economy? - Crevoisier, Olivier (My University, 2004)
Space has always been more or less present in economic theories. Nevertheless, traditional approaches, as well as the so-called new economic geography, introduce space subsequently. Economic theories are first built independently of spatial and temporal contexts, for example, through costs varying according to distance. The innovative milieus approach is based on the ideas that space—or, more precisely, territory—is the matrix of economic development and that economic mechanisms transform space. This article describes innovative milieus as an ideal type that articulates three paradigms: the technological paradigm, which stresses innovation, learning, and know-how as the most important competitive advantages; the organizational paradigm, which emphasizes the role of networks, competition, and rules of cooperation, as well as relational capital; and the territorial paradigm, which accounts for the role of proximity and distance and stresses the idea that competition occurs between regions. The originality of the innovative milieus approach is that it considers these three paradigms as a whole, thus providing a stabilized set of concepts that allow for an understanding of economic development processes in their space and time contexts.
Keywords: Innovative milieu; territory; innovation; learning